Firma de Convenio Marco de Cooperación Interinstitucional entre la Universidad Estatal de Bolívar y el Gobierno Autónomo Descentralizado del Cantón Babahoyo - DANNY LLIVI RUILOVA (2024)
The signing of the Interinstitutional Cooperation Framework Agreement between the State University of Bolívar and the Decentralized Autonomous Government of the Babahoyo Canton was carried out, for which the highest legal representatives, Dr. Arturo Rojas Sánchez, Rector of the Alma Mater Bolivarense and Eng. Gustavo Barquet Marún, mayor of the Babahoyo canton; signed said document, which was attended by Mgtr. María Vallejo, coordinator of the Disaster Risk Engineering degree at the Faculty of Health and Human Sciences of the UEB.